A feasibility study on the efficacy of a VR-based mindfulness intervention for dementia caregivers in the home environment: A pilot randomized control trial protocol - Qi Wang; Doris Yu; Gloria Wong; Daisy Zhang; Martin Knapp; Padmore Adusei Amoah; Jia Li; Cheng Shi (PLoS ONE, 2026)
Background Dementia affects over 50 million people worldwide, with numbers projected to triple by 2050. Informal caregivers—predominantly family members—provide the majority of daily care and exhibit disproportionately high rates of psychological distress, depressive symptoms, and perceived burden. Although mindfulness-based interventions (MBIs) have consistently demonstrated moderate-to-large effect sizes for improving caregiver mental health, traditional delivery modalities—face-to-face sessions or audio-guided home practice—are frequently constrained by low adherence, scheduling conflicts, and limited ecological validity within domestic settings. Immersive virtual reality (VR) technology offers a novel platform that can simulate restorative natural environments, minimise external distractions, and standardise mindfulness instructions while preserving temporal flexibility for users. Emerging evidence from non-caregiver populations suggests that VR-based MBIs may enhance engagement, retention, and affective outcomes compared with audio-only equivalents; however, data specific to dementia caregivers remain absent. This pilot study aims to explore the feasibility, acceptability, and effectiveness of a VR-based MBI in improving psychological status and caregiver-recipient relationship dementia caregivers. Methods This is a 3-arm, parallel, single-blinded, pilot randomised control trial comparing VR-based MBI with audio-based MBI and care-as-usual. The target sample includes 90 caregivers of community-dwelling persons with dementia. Each arm (n = 30) will receive an eight-week exercise with instructions, with outcome assessment at baseline, post-treatment, and a 2-month follow-up. Qualitative interviews will also be conducted to assess the feasibility and acceptance. The VR-based MBI group will engage in mindfulness exercises using a mobile app and VR technology, incorporating different natural environments. The primary outcome is the caregivers’ psychological status regarding depression, anxiety, and stress. The secondary outcomes include caregiver burden, mindfulness level, quality of life and caregiver-recipient relationship. Following intention-to-treat analysis, quantitative data on effectiveness will be analysed using between-group t-tests and group-by-time effect size (Cohen’s d). A six-step thematic analysis will be utilized for qualitative data. Conclusion The proposed intervention is expected to improve the psychological status of caregivers of people with dementia. The research may be helpful in promoting the well-being of people suffering from other psychological issues in the future. Trial registration ClinicalTrials.gov NCT07103434